Strategi Peningkatan Branding Usaha Mikro Kecil Dan Menengah Desa Pulosari Melalui Kegiatan Pengabdian Masyarakat - Maylinda Aristrinada Shyafira; Taysa Adila; Mariska Angelina; Eka Satya Nugraha; Dammandtyo Tegar Samudra; Mu’tasim Billah (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
MSMEs are particularly important to Indonesia's economic expansion. Up to 61.9% of the country's GDP is made up of MSMEs. When considered in part, the majority of MSMEs in the micro and small business category still struggle with numerous issues that prevent them from producing their best work. Many MSMEs lack a business strategy, making it difficult for MSMEs players to access the market effectively. In order to get the best outcomes, the goal of producing this article is to offer aid in maximizing the performance of MSMEs that have been active in Indonesia. The FGD (Focus Group Discussion) approach and socialization are used in the implementation method. The purpose of this journal was to pinpoint issues with MSMEs in Pulosari Village. The findings of this study demonstrate that MSMEs in Pulosari Village operate without a business strategy.